(untitled) (Revista de Medicina Clinica, 2022)
Introduction: Acute Leukemia (AL) is a heterogeneous neoplasm characterized by the monoclonal proliferation of immature cells. It is common in adults and its incidence increases with age. Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV2) is a viral disease that manifests itself with respiratory symptoms. The severity and complications are greater in patients with risk factors or other comorbidities such as hypertension, diabetes, cancer, cerebrovascular disease, chronic obstructive pulmonary disease, or chronic kidney disease. Some studies even showed that the impact of the disease and the risk of complications among patients with cancer or other hematological malignancies increases. Case Report: Next, we present a case of COVID-19 pneumonia in a 65-year-old man with newly diagnosed Acute Leukemia and Acute Respiratory Distress Syndrome (ARDS). Conclusion: Oncology investigator groups and other expert reviews recommend screening for SARS-CoV-2 in all patients with acute leukemia before starting therapy, regardless of symptoms.